The Brauer-Picard group of the representation category of finite supergroup algebras - Mombelli, Juan Martín (2014)
Fil: Mombelli, Juan Martín. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.